The Use of Peers in Assessment for Learning: A Case Study of Trainee Teachers at Bindura University of Science Education (BUSE), Zimbabwe - Young Mudavanhu; Christopher Mutseekwa (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
The study was an exploration of trainee teachers' understanding, perceptions of, and confidence in the use of peers in assessment for learning (AfL) at Bindura University of Science Education, Zimbabwe. Trainee teachers were enrolled in a programme that used a blended model of teaching and learning between February and June 2021. Trainees participated in online seminars and peer assessment in a course on curriculum development and completed questionnaire eliciting their attitudes toward peer assessment. A mixed-methods approach using both quantitative and qualitative methodologies was adopted. Quantitative data were analysed using descriptive statistics, mean item scores and the summated scores for the three constructs of confidence, benefits of and threats to peer assessment. Open-ended items were analysed qualitatively and emerging themes were reported. Summated scores of 4, meant trainees had positive attitudes toward peer assessment and believed in numerous benefits of using peer assessment. A summated mean score of 3 for threats to peer assessment meant trainee teachers had neutral views to the construct. Conflicting messages were evident. The same trainees who believed that peer assessment was useful still doubted sincerity of peers and preferred teacher assessment. Further research, using a larger population and sample and interviews to probe doubts in peer assessment, is recommended.